Quality of Life of Epileptic Children Using Pediatric “Quality of Life Inventory” TM (PedsQLTM) Assessment at RSUD Dr. Zainoel Abidin Banda Aceh - Hirsa Agriani; Anidar Anidar; Eka Yunita Amna; Bakhtiar Bakhtiar; Sulaiman Yusuf; Dora Darussalam; Syafruddin Haris (Budapest International Research in Exact Sciences (BirEx) Journal, 2021)
Epilepsy is a chronic disease that causes social function barriers that affect quality of life. Clinical factors, demographics, psychosocial, and anti-epileptic drugs are reported to affect the quality of life of people with epilepsy. This study aims to assess the quality of life of children with epilepsy who seek treatment at the IKA section of RSUDZA. This research is an observational analytic study with a cross-sectional design at the neurology polyclinic and inpatient Dr. RSUD. Zainal Abidin Banda Aceh for the period April-May 2021. The research subjects are 2-18 years old. Quality of life assessment using generic PedsQLTM 4.0. Multivariate analysis was tested using logistic regression test. It was found that 60 epilepsy patients participated in the study and obtained a quality-of-life disorder based on parent reports of 28.3%, and children's reports of 34.1%. There was no statistically significant relationship between demographic factors and children's quality of life based on parental reports (p< 0.05). In the children's report, it was found that demographic factors in the form of unexpected parenting were risk factors for impaired quality of life (p <0.05). Abnormal EEG picture is a clinically significant factor for impaired quality of life in children with epilepsy (p<0.05). This study concludes that patients with risk factors namely unexpected parenting, abnormal EEG affect quality of life.